Cardiovascular variability in Mexican patients with Parkinson's disease - Guillermo Delgado; Bruno Estañol; Mayela Rodríguez-Violante; Raúl Martínez-Memije; Óscar Infante-Vázquez; Nancy Bertado-Ramírez (Arquivos de Neuro-Psiquiatria)
Cardiovascular variability (CVV) has been evaluated in patients with Parkinson's disease (PD) in other countries and exhibit ethnic differences. Objective We investigated heart rate variability (HRV) and blood pressure variability (BPV) in Mexican patients with PD. Method We further compared HRV and BPV between this group and young healthy controls (YHC) in order to estimate, for the first time in our country, the magnitude of the difference. Twenty patients were examined. Time- and frequency-domain CVV parameters were studied during supine rest (SR), active standing (AS) and controlled breathing. These measurements were compared to those of 20 YHC. Results In the three conditions tested, our study showed a decrease in almost all HRV parameters in PD patients; on the contrary, decreased BPV parameters were found less frequently and only during SR and AS. Conclusion Our results indicate that HRV is impaired in PD. Some BPV parameters are also diminished.